A Versatile and Highly Efficient Method for 1‐Chlorination of Terminal and Trialkylsilyl‐Protected Alkynes. Issue 10 (12th February 2014) - Gulia, Nurbey; Pigulski, Bartłomiej; Charewicz, Marta; Szafert, Sławomir
Abstract A highly efficient one‐pot procedure for the preparation of 1‐chloroalkynes and 1‐chlorobutadiynes from terminal and trialkylsilyl‐protected precursors is reported. This convenient reaction, proceeding under mild conditions, utilizes N‐chlorosuccinimide as the chlorinating agent and tolerates a range of functional groups.